Drawing Arabians and other amazing horses - Young, Rae (North Mankato, Minnesota Capstone Press, 2014)
"Lively text and step-by-step instructions give an introduction to drawing horses"-
A gift from book Africa
Drawing
1 2 11 13
NEW_ZTN_GN
Keywords: Arabian horse in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Horses in art -- Juvenile literature